2014
DOI: 10.1111/pme.12375
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Interdisciplinary PSYMEPHY Treatment on Patients with Fibromyalgia: A Randomized Control Trial

Abstract: This study highlights the beneficial effects of an interdisciplinary treatment for FM patients in a hospital pain management unit. A 6-week interdisciplinary intervention showed significant improvement in key domains of fibromyalgia, as quality of life, pain, fatigue, rested, and anxiety at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…There is a benefit associated with the intervention because the scores in the FIQR subscale for symptoms revealed a global decrease in intensity, specifically pointing to significant differences in anxiety and pain items. Other studies showed similar findings of patient improvement after conducting different types of physical exercises [ 30 32 ]. However, the progress observed in our study cannot be attributed to physical exercise in the forest, given that all participants performed the same activity.…”
Section: Discussionsupporting
confidence: 61%
“…There is a benefit associated with the intervention because the scores in the FIQR subscale for symptoms revealed a global decrease in intensity, specifically pointing to significant differences in anxiety and pain items. Other studies showed similar findings of patient improvement after conducting different types of physical exercises [ 30 32 ]. However, the progress observed in our study cannot be attributed to physical exercise in the forest, given that all participants performed the same activity.…”
Section: Discussionsupporting
confidence: 61%
“…Subjects in the FMS sample scored an average of 88.38 (SEM 2.72) on the FIQ (data summarized in Table 1 ), which was slightly above the reported values of ca. 76 by studies in this geographic area [ 61 62 ]. Ongoing pain intensity was 8.89 (SEM .98) on the VAS, and scores on the Brief Pain Inventory averaged 7.39 (SEM .37), which can be considered as indicative of severe clinical pain with high interference with daily function.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the existence of a relationship and reciprocal influence between sleep disorders and the pain threshold increased widespread pain, more fatigue, and negative mood . Research has shown the efficacy of psychological treatments improving several clinical manifestations of pain . Several intervention programs have been developed for the simultaneous treatment for insomnia and pain, and these have shown positive results in sleep quality, pain interference, fatigue, and depression .…”
Section: Introductionmentioning
confidence: 99%